Imaging in vivo secondary caries and ex vivo dental biofilms using cross-polarization optical coherence tomography - Lenton, Pat; Rudney, Joel; Chen, Ruoqiong; Fok, Alex; Aparicio, Conrado; Jones, Robert S. (Dental materials, 2012)
Conventional diagnostic methods frequently detect only late stage enamel demineralization under composite resin restorations. The objective of this study is to examine the subsurface tooth–composite interface and to assess for the presence of secondary caries in pediatric patients using a novel Optical Coherence Tomography System with an intraoral probe. A newly designed intraoral cross polarization swept source optical coherence tomography (CP-OCT) imaging system was used to examine the integrity of the enamel–composite interfaces in vivo. Twenty-two pediatric subjects were recruited with either recently placed or long standing composite restorations in their primary teeth. To better understand how bacterial biofilms cause demineralization at the interface, we also used the intraoral CP-OCT system to assess ex vivo bacterial biofilm growth on dental composites. As a positive control, cavitated secondary carious interfaces showed a 18.2dB increase (p<0.001), or over 1–2 orders of magnitude higher, scattering than interfaces associated with recently placed composite restorations. Several long standing composite restorations, which appeared clinically sound, had a marked increase in scattering than recently placed restorations. This suggests the ability of CP-OCT to assess interfacial degradation such as early secondary caries prior to cavitation. CP-OCT was also able to image ex vivo biofilms on dental composites and assess their thickness. This paper shows that CP-OCT imaging using a beam splitter based design can examine the subsurface interface of dental composites in human subjects. Furthermore, the probe dimensions and acquisition speed of the CP-OCT system allowed for analysis of caries development in children.